1998
DOI: 10.1046/j.1365-2362.1998.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metformin on food intake in obese subjects

Abstract: Our study suggests that metformin administration is useful to inhibit FI and to lower BW and BF in obese non-diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
80
4
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 23 publications
9
80
4
2
Order By: Relevance
“…However, in our study no significant differences reported in BMI reduction due to dose escalation; this is in agreement with the Cochrane review of insulin sensitizing drugs for polycystic ovary syndrome, which showed no evidence of effect of increasing the dose of metformin on the degree of reduction in BMI [29]. Morin et al have demonstrated that insulin sensitizing therapy with metformin results in a decrease in leptin levels in patients PCOS [30]; meanwhile, Paolisso et al supported the data of Morin et al by showing that metformin decreases leptin in obese non-diabetics [31]. In the present study, serum leptin levels decreased in all patients groups after 3 months of treatment with metformin to levels lower than that reported in healthy controls, and as an exception to all evaluated parameters, the metformin-induced decrease in leptin levels was found to be dose-related, but only correlated with serum metformin due to administration of 2000 mg/day; this finding require further investigations.…”
Section: Discussionsupporting
confidence: 77%
“…However, in our study no significant differences reported in BMI reduction due to dose escalation; this is in agreement with the Cochrane review of insulin sensitizing drugs for polycystic ovary syndrome, which showed no evidence of effect of increasing the dose of metformin on the degree of reduction in BMI [29]. Morin et al have demonstrated that insulin sensitizing therapy with metformin results in a decrease in leptin levels in patients PCOS [30]; meanwhile, Paolisso et al supported the data of Morin et al by showing that metformin decreases leptin in obese non-diabetics [31]. In the present study, serum leptin levels decreased in all patients groups after 3 months of treatment with metformin to levels lower than that reported in healthy controls, and as an exception to all evaluated parameters, the metformin-induced decrease in leptin levels was found to be dose-related, but only correlated with serum metformin due to administration of 2000 mg/day; this finding require further investigations.…”
Section: Discussionsupporting
confidence: 77%
“…At the time before the operation, metformin was the only antidiabetic agent available which was expected to have effect on weight reduction. The evidence for metformin in obesity is insufficient (20), and few studies have reported the effect of metformin on obesity (21,22). In the present case, neither metformin nor fluvoxamine were affective to alter her appetite.…”
Section: Discussioncontrasting
confidence: 59%
“…Long-term clinical evaluations such as the DPP 18 or the FDPS 8 typically demonstrate an initial reduction in body weight during the early months of therapy, followed by a tendency for the effect to reverse during continued treatment. Furthermore, metformin has been shown to reduce food intake in studies of up to 15 days, 27,28 and the gastrointestinal side effects of metformin tend to appear early in therapy and may exert undue influence on the results of short-term studies. 29 This is not a formal meta-analysis.…”
Section: Data Sourcesmentioning
confidence: 99%